Single supply differential capacitive sensor with energy harvester compatibility - Che Mustapha, Nurul Arfah; Alam, A. H. M. Zahirul; Khan, Sheroz; Azman, Amelia Wong (IEEE, 2017)
This paper presents a single supply differential capacitive sensing technique suitable to be used with a hybrid energy harvester in providing power to the circuit. The proposed differential capacitive circuit is designed based on the available off-the-shelf components. Theoretical and experimental study has been carried out to observe the performance of the circuit for various excitation frequencies. Tests that were carried out include using excitation frequencies ranging with a 0.1 pF capacitance change. Results from 40 kHz up to 400 kHz show a high level of linearity up to a 0.999 R-squared value. Range of capacitance detection can be increased by controlling the feedback capacitor, Cf, and the filter components, Rd and Cd. The sensitivity range is from 0.004 to 0.122 mV per every fF change,with ± 5 % error. The circuit consumes 3.83 mW, with a 3.3 V supply voltage. This circuit is also suitable for a wireless sensing node application.